Regional abandoning of rural settlement in northern Sweden - Stone, Kirk H. (ERDKUNDE, 1971)
In recent times, the extensive scattered settlement area of northern Sweden has increasingly exhibited deserted settlements. With the help of two profiles, in which the abandoned farms were mapped in 1948 and 1958, the distribution is analyzed in more detail. The small settlements of 1-3 farms are particularly affected; but there are also deserted areas of 7-9 farms. This process is accompanied by a general population decline. The same phenomenon could be observed in combined farms and forestry operations. The depopulation places a heavy financial burden on local authorities and on the state government. The causes are, on the one hand, the relatively dense settlement of the area controlled by the Swedish state in the late 18th and early 19th centuries, on the other hand the increasing industrialization of Sweden, the rebellion of the young against the remoteness of the world, the improvement of general communication conditions. It can be assumed that the resettlement will continue.